DEVELOPMENT OF ANDROID-BASED INTERACTIVE MOBILE LEARNING TO LEARN 2D ANIMATION PRACTICE - Dindin Abidin; Nanny Mayasari; Abdullah Muamar; Erwinsyah Satria; Firman Aziz (Jurnal Scientia, 2023)
Mobile technology is one of the technologies that may be utilized in the learning process, which has become an important component of education. With mobile technology, learning may occur anywhere and at any time, without regard to location or duration. Mobile learning can also make students more engaged and independent in their learning, hence enhancing their independence in connection to their ability to utilize information technology. This research focuses on developing interactive mobile applications for 2D animation practice material at the vocational high school level because practice material is often difficult for students to comprehend; therefore, the existence of alternative mobile-based learning media can make difficult material easier for students to comprehend. Application features are adapted based on the needs analysis, and testing with students and subject matter experts demonstrates that interactive media applications for learning 2D animation practices based on android can be an alternative for students and teachers in supporting practicum material at school, so that the existence of alternative learning media can provide options for students to learn independently and improve their skills.